Unraveling Atomic‐Scale Origins of Selective Ionic Transport Pathways and Sodium‐Ion Storage Mechanism in Bi2S3 Anodes. Issue 11 (17th October 2022) - Cai, Ran; Zhang, Wenqi; Zhou, Jinhua; Yang, Kaishuai; Sun, Linfeng; Yang, Le; Ran, Leguan; Shao, Ruiwen; Fukuda, Toshio; Tan, Guoqiang; Liu, Haodong; Wan, Jiayu; et al.
Abstract: It is a major challenge to achieve a high‐performance anode for sodium‐ion batteries (SIBs) with high specific capacity, high rate capability, and cycling stability. Bismuth sulfide, which features a high theoretical specific capacity, tailorable morphology, and low cost, has been considered as a promising anode for SIBs. Nevertheless, due to a lack of direct atomistic observation, the detailed understanding of fundamental intercalation behavior and Bi2 S3 's (de)sodiation mechanisms remains unclear. Here, by employing in situ high‐resolution transmission electron microscopy, consecutive electron diffraction coupled with theoretical calculations, it is not only for the first time identified that Bi2 S3 exhibits specific ionic transport pathways preferred to diffuse along the (110) direction instead of the (200) plane, but also tracks their real‐time phase transformations (de)sodiation involving multi‐step crystallographic tuning. The finite‐element analysis further disclosed multi‐reaction induced deformation and the relevant stress evolution originating from the combined effect of the mechanical and electrochemical interaction. These discoveries not only deepen the understanding of fundamental science about the microscopic reaction mechanism of metal chalcogenide anodes but also provide important implications for performance optimization. Abstract : The investigation on sodium ions diffusion behavior and storage mechanism in anodes is quite critical for the performance optimization of sodium‐ion batteries. Here, by employing in situ high‐resolution transmission electron microscopy and density functional theory calculations, it is not only for the first time identified that Bi2 S3 exhibits specific ionic transport pathways, but also tracks their real‐time phase transformations (de)sodiation involving multi‐step crystallographic tuning down to atomic scale.